Pendampingan Bimbingan Belajar Akademik dan Religius di Dukuh Kejambon Kidul, Desa Sindumartani, Kecamatan Ngemplak, Kabupaten Sleman - Fatimah, Fatma Siti; Hidayah, Nila (Jurnal Atma Inovasia, 2021)
Abstract — Home tutoring assistance is needed during the Covid-19 pandemic, where all schools implement Distance Learning (PJJ) activities. The Ministry of Education and Culture issues regulations so that all learning activities at school are carried out at each student's home. The enactment of the PJJ policy makes parents have the responsibility to assist children while learning from home. In addition, the Covid-19 pandemic has an impact on TPA / TPQ activities at Dukuh Kejambon Kidul. For this reason, through tutoring assistance carried out by UAA 2021 Thematic KKN students as a form of community service, it can help children a total of 21 students, who have difficulty in the learning process at home and re-organize TPA / TPQ activities during the Covid-19 pandemic at the Kejambon Kidul hamlet in particular. RT 04 and 05. The learning methods applied during the morning class activities are lectures, fairy tales, question and answer, and practice. In conclusion can be drawn is that the activities of assisting academic, religious and educational guidance for Covid-19 for children can take place smoothly. Keywords — Tutoring Assistance, TPA / TPQ, Covid-19 Pandemic.  Abstrak — Pendampingan bimbingan belajar dari rumah sangat diperlukan di masa pandemi Covid-19 ini, dimana semua sekolah menerapkan kegiatan Pembelajaran Jarak Jauh (PJJ). Kemendikbud menerbitkan peraturan agar semua kegiatan pembelajaran di sekolah dilakukan di rumah masing-masing siswa. Berlakunya kebijakan PJJ membuat orang tua mempunyai tanggung jawab mendampingi anak selama belajar dari rumah. Selain itu, pandemi Covid-19 berdampak pada kegiatan TPA/TPQ di Dukuh Kejambon Kidul. Melalui pendampingan bimbingan belajar yang dilakukan oleh mahasiswa KKN Tematik UAA 2021 ini sebagai bentuk pengabdian masyarakat dapat membantu anak-anak sejumlah 21 siswa yang kesulitan dalam proses belajar di rumah  dan mengadakan kembali kegiatan TPA/TPQ pada masa pandemi Covid-19 ini di dukuh Kejambon Kidul khsusunya RT 04 dan 05. Metode pembelajaran yang diterapkan selama pelaksanaan kegiatan kelas pagi ialah ceramah, dongeng, tanya jawab, dan praktek. Simpulan yang dapat diambil adalah kegiatan pendampingan bimbingan belajar akademik, religius dan edukasi Covid-19 bagi anak- anak dapat berlangsung dengan lancar. Kata Kunci — Pendampingan Bimbingan Belajar, TPA/TPQ, Pandemi Covid-19.